Analisis Pengaruh Game Online Terhadap Perilaku Siswa SD Negeri 3 Petungsinarang Bandar - Didik Kurniawan; Happy Agustiani (Journal on Education, 2024)
This study investigated how online games affect student behavior in SD Negeri 3 Petungsinarang, Bandar District, Pacitan Regency, East Java. This research was conducted through survey method. This study involved all students in grades IV, V, and VI of SD Negeri 3 Petungsinarang Bandar. In total, 26 students from grades IV, V, and VI of SD Negeri 3 Petungsinarang Bandar were taken as samples, and a simple random sample method was used. The instrument is a questionnaire with a rating scale and Likert scale. Questionnaires are used to collect data. Simple linear regression analysis is used to present the data. The results showed that the value of fcount (2.471) was greater than ftable (0.388252), and the significant level of α = significant regression of 0.05. Therefore, the test results resulted in a regression equation Y = 39,120 + 0.249, which shows that online games affect student behavior in grades IV, V, and VI of SD Negeri 3 Petungsinarang Bandar District. The constant 39.120 indicates that if the value of the online game is 0, then the student's behavioral value (Y) is equal to 39.120. The positive relationship between the online game variable (X) and the student behavior variable (Y) is indicated by a positive value The higher the student's score in an online game is characterized by the lower the student's interest in the game, and vice versa. The higher the score, the better the student's behavior.